KAM Theory for Partial Differential Equations (Analysis in Theory and Applications, 2019)
In the last years much progress has been achieved in KAM theory concerning bifurcation of quasi-periodic solutions of Hamiltonian or reversible partial differential equations. We provide an overview of the state of the art in this field.
Keywords: KAM for PDEs; quasi-periodic solutions; small divisors; infinite dimensional Hamiltonian and reversible systems; water waves; nonlinear wave and Schrödinger equations; KdV.